The effect of an online video intervention 'Movie Models' on specific parenting practices and parental self-efficacy related to children's physical activity, screen-time and healthy diet: a quasi experimental study - Sara De Lepeleere; Ilse De Bourdeaudhuij; Greet Cardon; Maïté Verloigne (BMC, 2017)
Abstract Background In children, being sufficiently physically active, having low levels of screen-time and having a healthy diet are largely influenced by parenting practices. Children of parents applying positive parenting practices are at lower risk for overweight and obesity. Therefore, we investigated the effect of a health promoting online video intervention for parents ('Movie Models') on children's physical activity (PA), screen-time and healthy diet, and on specific parenting practices and parental self-efficacy related to these parenting practices. The online videos are delivered to parents of primary schoolchildren, and were based on real-life scenarios. Methods A two-armed, quasi experimental design was used. Parents of primary schoolchildren were recruited between November and December 2013 by spreading an appeal in social media, and by contacting primary schools. Participating parents were predominantly of high socio-economic status (SES) (83.1%), and only 6.8% of children were overweight/obese. Intervention group participants were invited to watch online videos for 4 weeks. Specific parenting practices, parental self-efficacy, PA, screen-time and healthy diet of the child were assessed at baseline (T0), at one (T1) and at four (T2) months post baseline. Repeated Measures (Multivariate) ANOVAs were used to examine intervention effects. The potential moderating effect of age and gender of the child and parental SES was also examined. Results Between T0 and T2, no significant intervention effects were found on children's PA, screen-time or healthy diet. Most significant intervention effects were found for more complex parenting practices (e.g., an increase in motivating the child to eat fruit). Subgroup analyses showed that the intervention had more effect on the actual parenting practices related to PA, screen-time and healthy diet in parents of older children (10-12 years old), whereas intervention effects on parental self-efficacy related to those behaviors were stronger in parents of younger children (6-9 years old). Conclusions 'Movie Models' was effective in increasing some important parenting practices and parental self-efficacy related to PA, screen-time and healthy diet in children. Therefore, the current study is an important first step in promoting effective parenting-related factors, and possibly increasing children's healthy diet and PA, and decreasing screen-time. Trial registration NCT02278809 in ClinicalTrials.gov on October 28, 2014 (retrospectively registered).